PERBANDINGAN HAMBATAN FINANSIAL PADA SEBELUM DAN SETELAH JAMINAN KESEHATAN DI INDONESIA - Putri Listiani; Julita Hendrartini; Dibyo Pramono (Journal of Health Service Management, 2019)
Background: Healthcare spending in Indonesia is still dominatedby out-of-pocket (OOP) system (45.1% in 2014). The high number of OOP in Indonesia is feared to cause financial burden tosociety and result in the failure of the financial protection functionof a health system, whereby Indonesia is in a scheme to achieveUniversal Health Coverage through the Universal Health Coverageprogram.Objective: This study aimed to compare the financial burden dueto OOP on before and after JKN and its determinants.Methods: This was a quantitative study that examines secondarydata, including Social Economic National Survey (Susenas) data in2013 and 2015 with cross sectional design. The unit of analysisin this study was households. Analysis conducted in this researchwas univariable, bivariable, and multivariable analysis. Multivariabletest using Logistic Regression Test was conducted to find out therelationship between the financial burden due to OOP with its determinants.Results: There was a decrease in the proportion of householdsexperiencing catastrophic health care expenditure was 0,59% in 2015. Households on before implementation of JKN period tend to face catastrophic health expenditure than households on afterimplementation of JKN period (OR= 2,29). Determinants affectingcatastrophic health expenditure in Indonesia were the number ofhousehold member, educational status of the head of household,the presence of toddler, the presence of elderly in the household,the location of the household residence, the economic status of thehousehold, the ownership of the health insurance, and the utilizationof health services.Conclusion: Utilization of inpatient health care services was themost contributing factor to catastrophic health expenditure. House-holds that use inpatient care had a catastrophic health care spend-ing risk of 26,78 times greater than non-accessed households